Orkes Gambus Himpunan Remaja Karya di Canggu, Batu Brak, Lampung Barat - Muhammad Randi Dimas Prayoga; Erizal Barnawi; Bian Pamungkas (Institut Seni Indonesia Denpasar, 2022)
Purpose: This study aims to describe the form of presentation of the Orkes Gambus HRK and a description of the structural analysis of the Janji Sebudi, Dang Cawa Khua, Gekhing, Mak Kesiwan and Seandanan song which is a legendary old song by HRK created by Basnal Maas. Research Methods: Qualitative research based on case studies. Sources of data in this study were obtained through interviews with the performers of the Orkes Gambus HRK, field observations, and documentation in the form of audio recordings transcribed into block notation as material for analyzing the form and structure of songs that are often presented by the HRK group. The song was analyzed using the theory of Karl Edmund Prier in his book entitled Ilmu Bentuk Musik. Results and discussion: The results of this study indicate that there are two aspects of presentation in the Orkes Gambus HRK performance, namely the form of musical presentation and the form of non-musical presentation. The form of musical presentation is in the form of instruments consisting of piul (violin), Gambus, Ketipung, Tambourines, Electric Bass, and Electric Guitars which are played on one of the legendary populer songs by HRK. The form of non-musical presentation includes the place of presentation, supporters, time, players, costumes, and loudspeakers. Implication: This research can contribute to science, as a written documentation of the typical art of West Lampung, namely the Orkes Gambus.